Laboratory manual for exercise physiology - Haff, Gregory, ....-; Dumke, Charles, ....- (Champaign : Human Kinetics, 2018)
Laboratory Manual for Exercise Physiology, Second Edition With Web Study Guide, provides guided opportunities for students to translate their scientific understanding of exercise physiology into practical applications in a variety of settings. Written by experts G. Gregory Haff and Charles Dumke, the text builds upon the success of the first edition with full-color images and the addition of several new interactive lab activities in the web study guide. The revitalized second edition comprises 16 laboratory chapters that offer a total of 49 lab activities. Each laboratory chapter provides a complete lesson, including objectives, definitions of key terms, and background information that sets the stage for learning. Each lab activity supplies step-by-step procedures, providing guidance for those new to lab settings so that they may complete the procedures. New features in this edition include the following: An updated web study guide that contains 10 interactive lab activities to enhance student learning, including video that helps simulate the experience of performing the labs in the real world A completely new laboratory chapter on high-intensity fitness training that includes several popular intermittent fitness tests that students can learn to perform and interpret An appendix that helps estimate the oxygen cost of walking, running, and cycling Full-color printing throughout